New records of the Kinkajou, Potos flavus (Schreber, 1774) (Mammalia, Carnivora) in the Cerrado - Jefferson Eduardo Silveira Miranda; Fabiano Rodrigues de Melo; Marluci Baldo Fachi; Seixas Rezende Oliveira; Ricardo Keichi Umetsu (Check List, 2018)
We provide new records of Potos flavus from 2 localities in the states of Goiás and Mato Grosso, central Brazil. These records extend the geographical distribution of this species in the Cerrado biome and highlights the importance of future research on this species. These new distributional data may contribute to a re-evaluation of its conservation status.